Birds : the art of ornithology - Elphick, Jonathan (New York : Rizzoli, 2015)
This remarkably beautiful volume gathers together a selection of the most important and vibrant ornithological art from Londons Natural History Museum. Birds tells the remarkable story of the development of ornithological art through the ages, from the earliest images of birds in the Renaissance, through the Age of Exploration, to the present day. Brilliantly reproduced original artworks by such renowned artists as Audubon, Gould, MacGillivray, Thorburn, and Wolfe are included.The lively accompanying text tells the story of how ornithological art grew out of the naturalistic tradition of European painting to become a genre on its own, where the artists focus on aesthetic appeal was married to the scientists need for precision and detail. Many of the works reproduced in this volume have never before been published. The detailed text interweaves science, art history, biography, exploration, and travel to paint a vast and wondrous picture of the bygone world of artist-scientists, exotic birds, and faraway lands. It makes a perfect gift for anyone who loves fine prints and drawings or has an interest in nature or birding.
Includes bibliographical references and index.
Keywords: Ornithological illustration -- History; Birds in art -- History; Animal painters. -- Biography